Outbreaks of Campylobacteriosis Caused by Drinking Raw Milk in Japan: Evidence of Relationship Between Milk and Patients by Using Whole Genome Sequencing - Ohno, Yuta; Sekizuka, Tsuyoshi; Kuroda, Makoto; Ikeda, Tetsuya (Foodborne pathogens and disease, 2023)
Raw milk may contain some infectious bacteria and usually requires pasteurization before drinking. In this study, we report rare outbreaks of campylobacteriosis associated with raw milk in Japan, and the application of whole genome sequencing (WGS) to studies on foodborne diseases. In August 2018, there were three outbreaks of campylobacteriosis, presumably caused by the consumption of unpasteurized raw milk, derived from the same farm; thus, these three outbreaks seemed to be associated with a single contaminant at the farm. Therefore, we analyzed isolates obtained at the three locations using several genetic methods. The sequence type of each isolate, revealed by multilocus sequence typing, was ST-61, and the profile determined using pulsed-field gel electrophoresis was the same; however, neither method could distinguish these from previously obtained strains. Subsequently, we performed WGS and single nucleotide variant (SNV) analysis that provided evidence of clonality, indicating that contamination was attributed to the farm. As in this study, evidence suggests that SNV analysis provides molecular biological support in cases with sufficient epidemiological information. Hence, similar analytical methods may be used in other sporadic cases to elucidate the relevance of the cases.